A year of COVID: The evolution of labour market and financial inequalities through the crisis - Thomas F. Crossley; Paul Fisher; Peter Levell; Hamish Low (Institute for Fiscal Studies (IFS), 2021)
We use new, high-quality UK panel data to document the economic impacts of the COVID-19 pandemic at an individual level, from April 2020 to March 2021. We focus on where and to what extent pre-existing labour market and financial inequalities have been exacerbated. Our story is more nuanced than earlier papers focusing on the start of the pandemic. To March 2021 some inequalities worsened, but others did not, and in some cases, a widening of labour market inequalities in the first wave of the pandemic was subsequently reversed. We find no evidence of divergence in employment outcomes by gender. On the other hand, the first wave of the pandemic impacted the employment of ethnic minorities, the young, and those with less formal education, but these differential impacts had largely abated by March 2021. By various measures, financial position and living standards strengthened, not only for the affluent, but also for middle deciles of the long-run income distribution, although those at the very bottom of the income distribution were more likely to report a decline in net wealth over the course of the pandemic.
Keywords: C83; D31; J63; 330; COVID-19; Savings; Inequality